Regulation of Growth and Main Health-Promoting Compounds of Chinese Kale Baby-Leaf by UV-A and FR Light - He, Rui; Li, Yamin; Ou, Shuying; Gao, Meifang; Zhang, Yiting; Song, Shiwei; Liu, Houcheng (Frontiers in Plant Science, 2021)
Chinese kale baby leaves were hydroponically cultured under the basal light (Red: white LEDs = 2:3 at PPFD of 250 μmol·m−2·s−1) with different supplemental lighting, including individual ultraviolet-A (UV-A, 380 ± 10 nm, 20 μmol·m−2·s−1), far-red (FR, 735 ± 10 nm, 30 μmol·m−2·s−1) light, and their combination (UF) radiation in an artificial light plant factory. Effects of supplemental light qualities on morphology and physiology as well as health-promoting compounds of Chinese kale baby leaves were investigated. Application of UV-A and FR presented a positive effect on biomass, with a pronounced increase in petiole length, stem diameter, main stem length, and leaf area. Notably, plants under UF grew more vigorously than under other treatments. Higher levels of FRAP, vitamin C, total phenolic, and flavonoid were observed in plants under UV-A, while no striking changes or a decreasing trend recorded under FR and UF. Moreover, UV-A enhanced the glucosinolates (GLs) accumulation in Chinese kale baby leaves by increasing the predominant GLs (glucoraphanin and glucobrassicin) contents. RT-qPCR results indicated that UV-A upregulated the gene expressions of transcription factors and core structure genes related to GLs biosynthesis. However, downregulated or unchanged gene expressions of GLs biosynthesis-related genes in Chinese kale baby leaves were observed in FR and UF. Therefore, UV-A was benefited for the production of functional substances, while FR was conducive to a significant increase in crop yield. The combination of UV-A and FR, as a balance between yield and production of secondary metabolite, provided a new perspective for the application of artificial light in horticultural crop production.